FRI0231 The first report of significant increase of body mass index in rheumatoid arthritis patients treated with tofacitinib during 12-month follow-up. (15th June 2017) - Novikova, D; Kirillova, I; Luchikhina, E; Markelova, E; Udachkina, H; Demidova, N; Misiyuk, A; Popkova, T; Volkov, A; Denisov, L; Karateev, D
Abstract : Objectives: to evaluate the effects of tofacitinib (TOFA) on cardiovascular risk factors (CVRF) in rheumatoid arthritis (RA) patients (pts). Methods: After 12-m follow-up the CVRF dynamic was assessed in 28 RA pts treated with TOFA (22 women, median age 54 [40; 62] years, disease duration 39.5 [16.5; 60.0] m, moderate to high activity (DAS28 - 5.1 [4.6; 6.0], SDAI – 26 [21; 34]), positive for ACCP (75%)/RF (79%), who were non-responders to MTX at least 15 mg/week and/or other synthetic DMARDs and biologic DMARDs. TOFA therapy was started in all pts with dose 5 mg BID per os followed by the dose escalation to 10 mg BID in 8 (29%) pts. TOFA used in combination with MTX in 27 (96%) pts, leflunomide in 1 (4%). Low-dose oral corticosteroids (<10 mg/day prednisone or equivalent) were received by 9 (35%) pts. Remission or low disease activity was achieved in 55% pts (DAS28), 77% (SDAI). At baseline the most of pts had multiple CVRF and subclinical organ damage. Cardioprotective therapy received 16 (57%) pts (beta-blockers – 7, angiotensin II receptor type 2/ACE inhibitors – 11, statins – 11, dihydropyridine calcium channel blockers – 7). Results: The incidence rate of arterial hypertension (67% vs 70%), overweight (57% vs 72%), abdominal obesity (61% vs 68%), physical inactivity (64% vs 47%), smokers/ex-smokers (25%/21% vs 21%/25%), menopausal status (59% vs 59%), DM type 2 (7% vs 7%), mSCORE≥5% (21% vs 28%), subclinical carotid atherosclerosis (64% vs 64%), cardiac heart failure with preserved ejection fraction (7% vs 7%) did not change significantly. Blood pressure remained stable over time except 1 pt. An increase in body mass index (BMI) was observed from 26.2 [22.9; 28.9] to 26.7 [24.0; 30.1], p<0.001, waist circumference from 86 [76;97] to 91 [80; 103], p=0, 001. The increase of BMI <5% was observed in 11 (39%) pts, 5% - 10% - 7 (25%), >10% - 6 (21%). The normal BMI remained in 7 (25%) pts, overweight – 9 (32%), obese class I – 3 (11%), the rest of pts passed to a higher category of BMI (from normal BMI to overweight – 4 (14%), from overweight to obese class I – 1 (4%), from obese class I to obese class II – 1 (4%)) and only 1 pt went from underweight to normal BMI (4%). The change in BMI correlated negatively with DAS 28, SDAI at baseline (r=-0.6, p<0.001). BMI dynamic was independent of TOFA dose, achieving RA activity, dynamic of DAS 28, SDAI, use of cardioprotective therapy. Dynamic of lipid levels depended on statins treatment. An increase in HDL-C level from 1.35 [0.88; 1.91] to 1.90 [1.64; 2.17], p<0.05, a decrease in LDL-C level from 3.75 [3.11; 4.40] to 2.60 [2.55; 2.93], p<0.03 was observed in pts treated with statins (n=11). An increase in total cholesterol level from 4.60 [4.14; 6.41] to 5.45 [4.56; 6.64], p=0, 001 was observed in pts who didn't receive statins (n=17). The change in HDL-C level correlated negatively with dynamic of DAS 28, SDAI (r=-0.4, p<0.05). Conclusions: TOFA therapy of RA pts contributes to dramatical increase of BMI. Greater BMI dynamic associated with higher disease activity at baseline. BMI dynamic was independent of achieving RA activity and dynamic of DAS 28, SDAI. Co-administration TOFA and statins resulted in significant favorable changes of LDL-and HDL-cholesterol levels. Disclosure of Interest: None declared